Dampak dari fitur-fitur gawai yang bisa mempengaruhi pola pikIr remaja - Silviasari, Nelli (Maliki Interdisciplinary Journal, 2024)
Apart from drugs, there is social media that makes it difficult for anyone to live without a device, especially teenagers. From young or old, young or old, poor or rich, all must have electronic media. Social media has many benefits for life, but it also has a very detrimental negative impact, if there are no restrictions on its use. From some of the horrors that can be negative from social media, actually what is the problem now is that many parents neglect to supervise the use of social media in children. As a result of this negligence, many children are addicted to social media to the point that it interferes with their education, mindset, and can interfere with their mental health (stress, depression, psychology). The research method used was a literature review, 9 relevant articles were found to be reviewed and analyzed with the impact of gadget features that can influence adolescent mindsets. With data sources obtained through the Google Scholar website, publish or perish websites, and other websites. The data is in the form of journals, articles, documents and e-books.